Optic, acoustic and acousto-optic properties of tellurium in close-to-axis regime of diffraction. (26th September 2017) - Voloshinov, V B; Khorkin, V S; Kulakova, L A; Gupta, N
Abstract: We examined the optic, acoustic, photoelastic and acousto-optic (AO) properties of single crystal tellurium. We also determined the Bragg angle dependences on the acoustic frequency at 10.6 μ m. The phenomenon of optical activity and its influence on the Bragg matching condition during anisotropic diffraction near the optic axis of the crystal are discussed in detail. Based on the results of our calculations, we designed, fabricated and characterized an AO cell to determine parameters of the anisotropic interaction with longitudinal acoustic waves propagating along the X axis in the crystal. In our experiments, we also measured the value of one of the important photoelastic coefficient in tellurium, p 41  = 0.14 ± 0.01 and demonstrated that this coefficient determines the efficiency of the anisotropic diffraction in the employed geometry.